Rational design of TiO2/MnMoO4/MoO3 nanocomposites: Visible-light-promoted photocatalysts for decomposition of tetracycline with tandem n-n heterojunctions - Pournemati, Khadijeh; Habibi-Yangjeh, Aziz; Khataee, Alireza (Elsevier, 2022)
In this research, MnMoO4 and MoO3 nanoparticles were simultaneously integrated with TiO2 particles by reflux method preceded by calcination step. The synthesized nanocomposites containing tandem n-n heterojunctions showed superior efficiency in photodegradation of tetracycline (TC) antibiotic and three toxic dyes including rhodamine B (RhB), methylene blue (MB), and malachite green (MG). The degradation rate constant of TC, MB, MG, and RhB over the optimum photocatalyst was 50.4, 32.2, 42.2, and 34.5 times more than pristine TiO2, respectively. The superior activity of the ternary photocatalyst was assigned to more generation of charges and efficacious separation and migration of electron/hole pairs, which were corroborated by UV-vis DRS, PL, EIS, and photocurrent density analyses. This study revealed that the novel ternary TiO2/MnMoO4/MoO3 photo -catalysts are very promising materials for photodegrading industrial effluents in the environment.
Keywords: TiO2; MnMoO4; MoO3; Tandem n-n heterojunctions; Tetracycline photodegradation; Photocatalytic performance